2020
DOI: 10.31557/apjcp.2020.21.6.1835
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Time Intervals for Diagnosis of Colorectal Cancer: A Hospital Based Study in Khon Kaen, Thailand

Abstract: Background: Colorectal cancer (CRC) is among the five-leading cancers in Thailand. Delayed diagnosis is crucial for undermining the prognosis of the patients. This study aims to evaluate the factors associated with the time interval for diagnosis (TID). Methods: A cross-sectional analytical study of 191 CRC patients with histological confirmation who were undergoing treatment in the tertiary hospital in Khon Kaen Province was conducted. The data were obtained by intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…Four smaller studies [ 53 , 64 , 72 , 78 ] reported intervals greater than 350 days and appeared to be outliers ( Fig 4 ). Mukherji et al [ 53 ] was a single center study of 32 patients <25 years of age in India and reported a mean of 355.9 days from symptoms onset to presentation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Four smaller studies [ 53 , 64 , 72 , 78 ] reported intervals greater than 350 days and appeared to be outliers ( Fig 4 ). Mukherji et al [ 53 ] was a single center study of 32 patients <25 years of age in India and reported a mean of 355.9 days from symptoms onset to presentation.…”
Section: Resultsmentioning
confidence: 99%
“…Foppa et al [ 78 ] reported mean time from symptoms onset to diagnosis of 416.7 days< for 101 Italian patients <40 years presenting to three tertiary centers. Finally, Rittitit et al [ 72 ] was a single-center study of 23 patients in Thailand and reported the longest interval of any study (median 442 days from symptom onset to diagnosis).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The regression coe cients were described using the Geometric Mean Ratio (GMR (CI95%)), following a similar approach performed in another study [22]. This allows for the interpretation of results in a manner akin to measures of association in epidemiology.…”
Section: Types Of Analysis and Statistical Methods Usedmentioning
confidence: 99%